Adjuvant Chemotherapy in Resected Lung Cancer: Two-Year Experience in a University Hospital - Nicole Bouchard; Francis Laberge; Bruno Raby; Sylvie Martin; Yves Lacasse (Canadian Respiratory Journal)
BACKGROUND: Randomized trials have confirmed the benefits of adjuvant chemotherapy in improving survival in resected early-stage non-small-cell lung cancer (NSCLC). The extent to which these results have translated into clinical practice is unknown.